1984
DOI: 10.3758/bf03198310
|View full text |Cite
|
Sign up to set email alerts
|

Semantic satiation affects category membership decision time but not lexical priming

Abstract: Experiments 1 and 2 examined the effects of semantic satiation on category membership decision latency. Subjects overtly repeated the name of a category either 3 or 30 times, and then decided whether or not a target exemplar was a member of the repeated category. Experiment 1 obtained some evidence that member decisions are slower and nonmember decisions are faster following 30 repetitions, but only the interaction was reliable. Experiment 2 confirmed only that member decisions are slower following satiation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
119
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(129 citation statements)
references
References 22 publications
6
119
4
Order By: Relevance
“…These results were inconsistent with previous studies demonstrating a loss of meaning of repeated words (e.g., Smith, 1984;Smith & Klein, 1990;Wertheimer & Gillis, 1958) and the elimination of semantic priming effects due to extensive prime repetition (e.g., Neely et al, 1998;Pitzer & Dagenbach, 2001). While these results indicate that priming is unaffected by target repetition at response, further research is required to examine the impact of target repetition during the actual RSVP task.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…These results were inconsistent with previous studies demonstrating a loss of meaning of repeated words (e.g., Smith, 1984;Smith & Klein, 1990;Wertheimer & Gillis, 1958) and the elimination of semantic priming effects due to extensive prime repetition (e.g., Neely et al, 1998;Pitzer & Dagenbach, 2001). While these results indicate that priming is unaffected by target repetition at response, further research is required to examine the impact of target repetition during the actual RSVP task.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies have reported the subjective loss of meaning of a word (semantic satiation) through prolonged exposure to and repetition of a word (e.g., Smith, 1984;Smith & Klein, 1990;Wertheimer & Gillis, 1958). For example, Smith (1984) used a category membership task and required participants pronounced the category name (e.g., fruit) 3 or 30 times as it appeared on the computer screen. After the final repetition, a target word (that was either related or unrelated to the category name e.g., apple or hawk) appeared on the screen.…”
mentioning
confidence: 99%
“…Critically, member decisions were actually slower following 30 repetitions of the category than after only 3 (see also Balota &Black, 1997, andSmith &Klein, 1990). Using similar methods, satiation effects have been observed with faces as the repeated stimuli (Lewis & Ellis, 2000), suggesting that this phenomenon may be a general consequence of massive repetition, at least for measures of accessibility taken immediately after repetition.…”
mentioning
confidence: 81%
“…It is more likely that worrisome thinking is the immediate cognitive avoidance response to such images when they do occur. The demonstrated suppressive effects of worry on somatic anxiety could also be due to the fact that worry uses up significant amounts of attentional resource (Mathews, 1990), is difficult to shift away from (Parkinson & Rachman, 1981), insulates its thoughts from affective meaning through the semantic satiation inherent in its repetitive verbal activity (Smith, 1984), and creates less mismatch between information expected and • information received (Gray, 1982).…”
Section: Worry Suppresses Somatic Anxietymentioning
confidence: 99%